A systematic review of the published literature on team-based learning in health professions education. (2nd December 2017) - Reimschisel, Tyler; Herring, Anna L.; Huang, Jennifer; Minor, Tara J.
Abstract: Purpose: Summarize the published literature on team-based learning (TBL) in health professions education (HPE) using the TBL conceptual framework to identify gaps that can guide future research Methods: PubMed, Web of Science, ERIC, and Google Scholar were searched through May 2016 for English-language articles regarding the use of TBL in HPE. Reviewers independently extracted data and coded for the seven elements in Michaelsen's Model of TBL. Results: A total of 118 articles met inclusion criteria. The number of articles published yearly on TBL has grown steadily, more than tripling between 2011 and 2016. Most studies (55; 47%) involved undergraduate medical students and took place in the US (72; 61%). The most commonly studied framework component was Teacher and Learner Attitudes (97; 82%). Other commonly studied elements included Learning Outcomes (85; 72%) and Team Characteristics (25; 21%). Contextual Factors affecting TBL was addressed in one study. Conclusions: A substantial body of literature examines the effect that TBL has on traditional measures of achievement. However, many dimensions of TBL have not been well studied, including Teacher Decisions about TBL, Contextual Factors that affect TBL, Learners' Engagement, and Pattern of Engagement within Teams. Future research in these areas could determine the best use of TBL in HPE.